A sequential quadratically constrained quadratic programming method for unconstrained minimax problems - Jian, Jin-bao; Chao, Mian-tao (Journal of mathematical analysis and applications, 2010)
In this paper, a sequential quadratically constrained quadratic programming (SQCQP) method for unconstrained minimax problems is presented. At each iteration the SQCQP method solves a subproblem that involves convex quadratic inequality constraints and a convex quadratic objective function. The global convergence of the method is obtained under much weaker conditions without any constraint qualification. Under reasonable assumptions, we prove the strong convergence, superlinearly and quadratic convergence rate.